StandOut 2.0 : assess your strengths, find your edge, win at work - Buckingham, Marcus (Boston, Massachusetts : Harvard Business Review Press, 2015)
"In the years since publication of First, Break All the Rules and Now, Discover Your Strengths, millions have had the simple but powerful realization that to get the most out of people you must build on their strengths. And yet, as Marcus Buckingham astutely points out, even though the strengths-based approach is now conventional wisdom, the tools and systems inside organizations-performance appraisals, training programs, and succession planning systems-remain stubbornly remedial, exclusively focused on measuring skills, finding gaps, and attempting to plug them. It's a crisis for individuals and organizations, with management ideas and management practice utterly out of sync. That's about to change. StandOut 2.0 is a revolutionary book and tool that enables you to identify your strengths, and those of your team, and to act on them. The original StandOut provided top-notch management insights from one of the world's foremost authorities on strengths, as well as access to a powerful, cutting edge online assessment tool. Now, in addition to a much more powerful assessment, and a robust report on your most dominant strengths, StandOut 2.0 provides: - A StandOut profile, easily customized and exported, that you can use to present the very best of yourself to your team, and your company - Your own Personalized Strengths Channel, which, after taking the 15 minute assessment, will send you a weekly tip, insight, or technique, to help you do your best work this week - For team leaders, the ability to create a team dashboard including each member's StandOut profile, to help you make the right moves - Access to an entire strengths-based performance management system, including a check-in tool to capture priorities and track engagement; a survey tool to help you gauge what your team is thinking and feeling; and an evaluation tool to help reveal real-time performance levels of every single team member StandOut 2.0 is your indispensable guide and tool for building on your str
Your genius : find your edge and make it work for you -- The new StandOut assessment : what it measures, how it works, and how to take it -- How to stand out : three lessons for building your strengths -- "Whistles for everybody!" : how strengths-building accelerates innovation -- The nine strength roles : advisor, connector, creator, equalizer, influencer, pioneer, provider, stimulator, teacher -- Appendix : strengths assessment technical summary.
Includes index.
Print version record.
Keywords: Employee motivation; Creative ability in business; Ability; Success; Performance -- Psychological aspects; SELF-HELP / Personal Growth / Success; BUSINESS & ECONOMICS / Human Resources & Personnel Management; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Management; Creative ability in business; Ability; Employee motivation; Performance -- Psychological aspects; Success; BUSINESS & ECONOMICS / Reference; BUSINESS & ECONOMICS / Skills; elektronické knihy; electronic books